2012
DOI: 10.1111/j.1601-183x.2012.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

The canid genome: behavioral geneticists' best friend?

Abstract: We review a range of studies on the genetic contribution to behavior in canid species. We begin by identifying factors that make canids a promising model in behavioral genetics and proceed to review research over the last decade that has used canids to identify genetic contributions to behavior. We first review studies that have selectively bred dogs to identify genetic contributions to behavior and then review studies that estimate heritability from populations of nonlaboratory bred dogs. We subsequently revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 136 publications
(311 reference statements)
2
22
0
Order By: Relevance
“…In accordance with previous studies (Mackenzie et al, 1986;Willis, 1995;Houpt and Willis, 2001;Houpt, 2007;Hall and Wynne, 2012), also the present meta-analysis has shown low general heritability of the categorised behavioural traits analysed. When compared with the previous reports, the novelty of this study lies in the fact that individual high values of heritability reported either for individual trait or traits within a study (e.g., Fält et al, 1982;Goddard and Beilharz, 1985;Kreiner et al, 1992;Schmutz and Schmutz, 1998;Wilsson and Sundgren, 1998;van den Berg et al, 2006b;Liinamo et al, 2007), or for a single dog breed (Kreiner et al, 1992;Schmutz and Schmutz, 1998) disappeared when statistical synthesis of the data across studies was applied.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous studies (Mackenzie et al, 1986;Willis, 1995;Houpt and Willis, 2001;Houpt, 2007;Hall and Wynne, 2012), also the present meta-analysis has shown low general heritability of the categorised behavioural traits analysed. When compared with the previous reports, the novelty of this study lies in the fact that individual high values of heritability reported either for individual trait or traits within a study (e.g., Fält et al, 1982;Goddard and Beilharz, 1985;Kreiner et al, 1992;Schmutz and Schmutz, 1998;Wilsson and Sundgren, 1998;van den Berg et al, 2006b;Liinamo et al, 2007), or for a single dog breed (Kreiner et al, 1992;Schmutz and Schmutz, 1998) disappeared when statistical synthesis of the data across studies was applied.…”
Section: Discussionsupporting
confidence: 93%
“…Behavioural differences between domestic dog breeds and between lines within breeds are known and have been also well documented (Mackenzie et al, 1986;Willis, 1995;Ostrander and Kruglyak, 2000;Houpt and Willis, 2001;Houpt, 2007;Hall and Wynne, 2012;Mehrkam and Wynne, 2014). In rare cases it has been reported that selective breeding for a few generations of dogs may result in apparently diverging behaviourally different strains or in eradicating or reducing the frequency of problematic behaviour (Murphree et al, 1974;Takeuchi and Houpt, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…So far, numerous genes have been mapped for morphological traits and diseases , but the identification of genes underlying behavioural phenotype is still lagging behind. However, several single nucleotide polymorphisms (SNPs), variable number of tandem repeats (VNTRs), and copy number variants of candidate genes relating to androgen, serotonin, dopamine, and other systems already have been sequenced (e.g., Héjjas et al, 2007b;van den Berg et al, 2008;Konno et al, 2011; for a review, see Hall & Wynne, 2012). Specific genes have been identified either by candidate gene approach (Héjjas et al, 2007a;Takeuchi et al, 2009a;Våge et al, 2010) or by genome-wide association studies (GWAS; Dodman et al, 2010;Tiira et al, 2012).…”
Section: Gene-behaviour Associationsmentioning
confidence: 99%
“…Since its genome was sequenced in 2005 (Lindblad-Toh et al, 2005) the dog has therefore become one of the most promising models for behaviour genetics (Hall and Wynne, 2012). By focusing on traits, which distinguishes breeds from each other or individuals within breeds, it is possible to reveal the underlying genetics of behavioural variation.…”
Section: From Phenotypic Variation To Geneticsmentioning
confidence: 99%